Islamic Higher Education and Science Integration - Hasbi Indra (Fakultas Agama Islam Universitas Wiralodra, 2020)
Humans now face many problems due to technological developments in this digital age. Islamic higher education students have the potential to be part of nation-building. This era is a free trade competition between nations in the world and requires human qualities. So Islamic higher education, one of the places to transfer values based on the Koran and Hadith, must form quality students so that they play an important role in their country. Students who study Islamic science, as well as secular science, aim to shape themselves on campus. In this era, students must have broader knowledge about science and economics and students have a spirit of entrepreneurship, as well as good competence and attitude. This quality can be achieved through lecturers who use integrated knowledge between Islamic perspectives and contemporary perspectives. This research is qualitative research with descriptive analysis through literature studies related to Islamic higher education, the challenges and how lecturers use integrated knowledge methods in the learning process.